Macrophages derived from gene-edited pigs pose resistance to multiple isolates of Porcine Reproductive and Respiratory Syndrome virus - Bardot, Rachel Erin (Kansas State University, 2017)
Porcine Reproductive and Respiratory Syndrome Virus (PRSSV) is one of the most economically important diseases in the global swine industry, costing producers an estimated $660 million annually. PRRSV is genetically diverse with a low replication fidelity, due to it being an RNA virus, resulting in multitudes of isolates being produced. This virus has a tropism for cells of the monocyte/macrophage lineage. Cluster of Differentiation 163 (CD163) is considered the primary PRRSV receptor located on porcine alveolar macrophages (PAMs). CRISPR/Cas9 technology was utilized to knock out CD163 via a frameshift mutation, resulting in pigs of the CD163 Null genotype. Also, a domain of porcine CD163 was deleted and replaced with the insertion of a CD163 homolog of human-like domain and neomycin cassette to serve as a genetic marker. This swap resulted in pigs that possessed a CD163L1 domain 8 mimic of porcine homolog human CD163-like (hCD163L-1) of SRCR domain 8. Previous work has demonstrated that CD163 Null pigs were resistant to one genotype 2 PRRSV isolate. An in vivo study was performed to observe whether hCD163L-1 pigs were also resistant to infection. Various diagnostic tests were performed to determine the presence or absence of PRRSV viremia levels in serum, CD163 receptor surface expression levels on PAMs, IgG antibody levels and haptoglobin (Hp) levels in serum. hCD163L-1 pigs did not support genotype 1 PRRSV replication, but were susceptible to genotype 2 PRRSV infections. In addition, in vitro infection experiments were performed on PAMs and macrophages derived from peripheral blood mononuclear cells (PBMCs) to determine resistance to multiple isolates. hCD163L-1 macrophages showed reduced infection with genotype 2 and no infection with genotype 1 PRRSV during in vitro infections. Null PAMs and PBMCs derived macrophages did not support infection towards any isolate of either PRRSV genotype.
Keywords: PRRSV; Macrophages; CRISPR/Cas9